Labour market outcomes of national qualifications frameworks in six countries - Allais, Stephanie (Taylor and Francis Group, 2017)
This article presents the major findings of an international study that attempted to investigate the labour market outcomes of qualifications frameworks in six countries – Belize, France, Ireland, Jamaica, Sri Lanka, and Tunisia, as well as the regional framework in the Caribbean. It finds limited evidence of success, but fairly strong support for the frameworks. The continued popularity of qualifications frameworks as a reform mechanism seems to be symptomatic of the ways in which transitions from education to work are in flux in many countries, coupled with the fragmented and complex systems of vocational provision in some of the countries. Even where such systems are not overly complex they have weak and possibly weakening relationships with work. Insufficient differentiation of different types of frameworks by policy makers obscures these factors, leading to misleading ideas about what frameworks can do in general. Extending existing typologies for the analysis of qualifications frameworks the paper argues that the French framework, where labour markets were the most regulated and collective bargaining had the widest reach, had the clearest relationships between qualifications and work. However, the qualifications framework did not seem to be the cause, but rather the effect of such relationships
Keywords: National qualifications; Frameworks; National vocational qualifications; Education/labour market relationships; Qualification reform; SDG-4: Quality education